ANALYSIS OF RESEARCHES ABOUT AMBASSADOR ERNAZAR MAKSUD OGLU (Scientific journal of the Fergana State University, 2023)
This article analyzes on the basis of literature of different periods the reasons, purpose, tasks and results of the Embassy of Ernazar Maksud ugli from Bukhara in Russia. The study also examines the history of relations between the Russian Empire and the Emirate of Bukhara and the benefits of these diplomatic relations. The article describes the history of the Russian Embassy, its composition and brief history based on the analysis of literature from different periods. The historiography of the Embassy is based on the literature of the Imperial, Soviet and independence periods. The historiographical analysis examines such issues as the reasons for the Embassy, its goals, and its results. In addition, the issue of the role of this Embassy in the development of diplomatic relations is being considered. A comparative analysis of the problem of political interests of the two States was made from this Embassy. In addition, the authors studied the conclusions of researchers about the long-term plans for the development of diplomatic relations. Historiographical analysis and scientific criticism of the research of different periods are carried out.